# ICSE Solutions for Chapter 5 Quadratic Equations Class 10 Mathematics

Question 1:  Solve: (2x/x – 3) + (1/2x + 3) + {(3x + 9)/(x - 3)(2x + 3)} = 0; x ≠ 3, x ≠ -3/2

Solution 1:
(2x/x – 3) + 1/(2x + 3) + {(3x + 9)(x + 3)(2x + 3)} = 0; x ≠ 3, x ≠ -3/2
⇒ {2x(2x + 3) + 1(x - 3) + 3x + 9}/{(x – 3)(2x + 3)} =  0
⇒ 4x2 + 6x + x – 3 + 3x + 9 = 0
⇒ 4x2 + 10x + 6 = 0
⇒ 4x + 4x + 6x + 6 = 0
⇒ 4x(x + 1) + 6(x + 1) =  0
⇒ (x + 1)(4x + 6) = 0
⇒ x + 1 = 0  or  4x + 6 = 0
⇒ x = -1 or x = -6/4 = -3/2(reject)

Question 2: Solve: (2x + 3)2 = 81

Solution 2:
(2x + 3)2 = 81
⇒ 2x + 3 = ±9
⇒ 2x + 3 = 9 and 2x + 3 = -9
⇒ 2x = 6 and 2x = -12
⇒ x = 3 and  x = -6

Question 3: Solve: a2x2 - b2 = 0

Solution 3: a2x- b2 = 0
⇒ (ax)2 - b2 = 0
⇒ (ax + b)(ax - b) = 0
If ax + b = 0 and  ax – b = 0
then x = -b/a and x = b/a

Question 4: Solve: x2 – 11/4x + 15/8 = 0

Solution 4: x2 – 11/4x + 15 = 0
⇒ {(8x2 - 22x + 15)/8} = 0
⇒ 8x2 - 22x + 15 = 0
⇒ 8x2 - 12x - 10x + 15 = 0
⇒ 4x(2x - 3) - 5(2x - 3) = 0
⇒ (2x - 3)(4x - 5) = 0
⇒  2x – 3 = 0 or 4x – 5 = 0
⇒  x = 3/2  or x = 5/4

Question 5:  x + 4/x = - 4; x ≠ 0

Solution 5:
x + 4/x = -4;
⇒ {(x2 + 4)/x} = - 4
⇒ x2 + 4 = - 4x
⇒ x2 + 4x + 4 = 0
⇒ (x + 2)2 = 0
⇒ x + 2 = 0
⇒ x = -2

Question 6: Solve: 2x4 - 5x2 + 3 = 0

Solution 6: 2x4 – 5x2 + 3 = 0
⇒ 2x4 - 3x2 - 2x2 + 3 = 0
⇒ x2(2x2 - 3) - 1(2x2 - 3) = 0
⇒ (2x2 - 3)(x2 - 1) = 0
If  2x2 – 3 = 0 or  x2 - 1 = 0
then x2  or  x2 = 1
⇒ x = ± √3/√2   or  x = ± 1

Question 7: Solve: x4 - 2x2 - 3 = 0.

Solution 7: x4 - 2x2 – 3 = 0
⇒ x4 - 3x2 + x2 - 3 = 0
⇒ x2(x2 – 3) + 1(x2 - 3) = 0
⇒ (x2 - 3)(x2 + 1) = 0
If  (x2 – 3) = 0 or  x2 + 1 = 0
then x2 = 3 or x2  = -1(reject)
⇒ x = ± √3

Question 8: Solve: 9(x2 + 1/x2) – 9(x + 1/x) – 52 = 0

Solution 8:
9(x2 + 1/x2) - 9(x + 1/x) – 52 = 0
Let (x + 1/x) = y
squaring on both sides
x2 + 1/x2 + 2 = y2
⇒ (x2 + 1/x2) = y2 – 2
Putting these values in the given equation
9(y2 - 2) – 9y - 52 = 0
⇒ 9y2 - 18 – 9y - 52 = 0
⇒ 9y2 - 9y - 70 = 0
⇒ 9y2 - 30y + 21y - 70 = 0
⇒ 3y(3y - 10) + 7(3y - 10) = 0
⇒ (3y - 10) (3y + 7) = 0
⇒ 3y – 10 = 0 or  3y + 7 = 0
⇒ y = 10/3 or y = -7/3
⇒ (x + 1/x)  = 10/3 or (x + 1/x) = -7/3
⇒ (x2 + 1)/x = 10/3 or (x2 + 1)/x = -7/3
⇒ 3x2 - 10x + 3 = 0 or 3x2 + 7x + 3 = 0
⇒  3x2 – 9x – x + 3 = 0
or
⇒ 3x(x – 3) – 1(x – 3) = 0 or x = (-7 ± √13)/6
⇒ (x – 3)(3x – 1) = 0
⇒ x = 3 and x = 1/3

Question 9: Solve: 2(x2 + 1/x2) - (x + 1/x) = 11

Solution 9:
2(x2  + 1/x2) – (x + 1/x) = 11
Let (x + 1/x) = y
squaring on both sides
x2  + 1/x2  + 2 = y2
⇒  x2  + 1/x2  = y2  – 2
Putting these values in the given equation
2(y2  - 2) - y = 11
⇒ 2y2 – 4 – y - 11 = 0
⇒ 2y2 – y – 15 = 0
⇒ 2y2 - 6y + 5y -15 = 0
⇒ 2y(y - 3) + 5(y - 3) = 0
⇒  (y - 3)(2y + 5) = 0
If  y – 3 = 0  or   2y + 5 = 0
then, y = 3  or  y = -5/2
⇒  x + 1/x = 3 or  (x + 1/x) = -5/2
⇒  (x2  + 1)/x = 3 or (x2  + 1)/x = -5/2
⇒  x2  – 3x + 1 = 0 or  2x2  + 5x + 2 = 0 or 2x2  + 4x + x + 2 = 0
⇒  x = (-3 ± √5)/2
or, 2x(x + 2) + 1(x + 2) = 0
or, (x + 2)(2x + 1) = 0
then x = -2 and x = -1/2

Question 10: Solve: (x2 – 1/x2) - 3(x – 1/x) – 2 = 0

Solution 10:  (x2 + 1/x2) - 3(x – 1/x) – 2 = 0
Let   (x – 1/x) = y
squaring on both sides
(x2 + 1/x2) – 2 = y2
⇒ (x2 + 1/x2) = y2 + 2
Puting these values in the given equation
(y2 + 2) - 3y - 2 = 0
⇒ y2 - 3y = 0
⇒ y(y - 3) = 0

If  y = 0 or y – 3 = 0
then y = 0 or y = 3
⇒ (x – 1/x) = 0 or (x – 1/x) = 3
⇒ (x2 – 1)/x = 0 or (x2 – 1)x = 3
⇒ x2 - 1 = 0 or x2 – 3x – 1 = 0
⇒ (x + 1)(x – 1) = 0
or ⇒ x = -1 and x = 1 or x = (3 ± √13)/2